Analysis of Induced Field in the Brain Tissue by Transcranial Magnetic Stimulation Using Halo-V Assembly Coil. (14th July 2022) - Sathi, Khaleda Akhter; Hosain, Md. Kamal; Hossain, Md. Azad
Abstract : As a noninvasive neuromodulation technique, transcranial magnetic stimulation (TMS) has already exhibited a great impact in clinical application and scientific research. This study presents a finite element method-based simulation of the Halo-V assembly (HVA) coil placed on the five-shell spherical human head model to examine the distributions of induced electric and magnetic fields. The performance of the designed HVA coil is evaluated by comparing the simulation results with the commercially available Halo-FO8 (HFA) assembly coil and standard single coils including the Halo and V coils. The simulation results indicate that the HVA coil shows an improved focality in terms of electric field distribution than the other single and assembly stimulation coils. Additionally, the effects of a magnetic shield plate and magnetic core on the designed HVA coil are investigated. Results indicate that the magnetic shield plate and magnetic core are proficient in further improving the stimulation focality. Therefore, the HVA TMS coil results in a safe and effective stimulation with enhanced focality of the target region as compared to the existing assembly coil.